From Market Orientation to Institutional Agility: Exploring Mediating Roles of Innovation and Learning Orientation in Private Higher Education - Hidayati, Arifah; Priyopradono , Bentar; Melati (Corolla International Conference, 2025)
This study analyzes the relationship between Market Orientation and Institutional Agility in private universities in Indonesia by exploring the mediating role of innovation and learning orientation. This study was developed from previous research on the performance and competitiveness of private universities in Bengkulu Province using a dynamic capabilities theory approach that emphasizes the importance of organizational capabilities in adapting to a dynamic environment. Data were collected through a survey of faculty and study program leaders using standardized instruments and analyzed using Structural Equation Modeling (SEM) to test the double mediation model. The results show that market orientation significantly affects institutional agility through innovation and learning orientation. These two mediating variables serve as the main mechanisms that enable universities to adapt to changes in the higher education market, technology, and student needs. These findings emphasize the importance of building a culture of innovation and continuous learning in strengthening the strategic responsiveness of private universities to competitive pressures and the digitization of education. The study contributes theoretically by expanding the understanding of the relationship between market orientation and institutional agility, and provides practical implications for university leaders in developing adaptive strategies based on innovation and learning.